2017
DOI: 10.1007/s00405-017-4566-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of satisfaction based on age and gender in functional and aesthetic rhinoplasty

Abstract: The aim of this study was to assess patients' satisfaction based on gender and age using the Rhinoplasty Outcomes Evaluation (ROE) post-rhinoplasty from both functional and aesthetic outcomes. The study design was a prospective observational study. A total of 103 patients who underwent Rhinoplasty were prospectively investigated from January 2011 through December 2013 at King Abdulaziz University Hospital in Riyadh, Saudi Arabia. The sample included 61 males (59.2%) and 42 females (40.7%). The overall mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
12
0
3
Order By: Relevance
“…Rhinoplasty (RP) is among the most commonly performed surgeries for both aesthetic and functional purposes (1). Most studies of RP have focused on the surgical technique, level of surgeon experience, development of complications, and revision rate (2,3) However, an assessment of RP from the patient’s perspective, in terms of satisfaction and quality of life, is equally important because these are the predominant factors indicating the success of RP, as well as its ultimate purpose (4,5).…”
mentioning
confidence: 99%
“…Rhinoplasty (RP) is among the most commonly performed surgeries for both aesthetic and functional purposes (1). Most studies of RP have focused on the surgical technique, level of surgeon experience, development of complications, and revision rate (2,3) However, an assessment of RP from the patient’s perspective, in terms of satisfaction and quality of life, is equally important because these are the predominant factors indicating the success of RP, as well as its ultimate purpose (4,5).…”
mentioning
confidence: 99%
“…The 3D-printed PCL is a ball-shaped prosthesis that serves as a biological scaffold that allows the growth of tissues within the tiny holes of the scaffold without interfering with blood circulation and therefore enhances the volume of the nasal tip [3,5]. Complete absorption of PCL occurs in approximately 36 months; however, no study has reported long-term follow-up of > 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The Rhinoplasty Outcome Evaluation questionnaire ( Fig. 2) was distributed to all patients included in the study [3]. Patients responded to 6 questions, and each question was answered on a scale from 0 (lowest satisfaction) to 4 (high satisfaction).…”
Section: ) Patient Survey As a Measure Of Subjective Levels Of Satismentioning
confidence: 99%
“…This result suggests that the surgeon should be aware of both the functional and the aesthetic issues associated with RP. The follow-up period varies widely among studies in the literature (1,2,(5)(6)(7)(8)(9). Izu et al (2) attributed the differences in ROE scores between postoperative day 15 and the third postoperative month to a decrease in postoperative edema at the later time point.…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoplasty (RP) is among the most commonly performed surgeries for both aesthetic and functional purposes (1). Most studies of RP have focused on the surgical technique, level of surgeon experience, development of complications, and revision rate (2,3) However, an assessment of RP from the patient's perspective, in terms of satisfaction and quality of life, is equally important because these are the predominant factors indicating the success of RP, as well as its ultimate purpose (4,5). Patient satisfaction with the results of RP is generally lower than with those of other facial aesthetic surgeries (6,7).…”
mentioning
confidence: 99%